A Systematic Review of Campus Characteristics Associated With Sexual Violence and Other Forms of Victimization. (July 2023) - Tashkandi, Yara; Hirsch, Jennifer S.; Kraus, Emily; Schwartz, Rachel; Walsh, Kate
Violence researchers have highlighted a need to understand connections between campus characteristics and violent victimization among students. Responding to those calls, we systematically reviewed research examining the characteristics of secondary and post-secondary educational settings associated with sexual violence and related victimization experiences, including dating/intimate partner violence, stalking, bullying, hate crimes, and crime more broadly. We screened 1124 quantitative and qualitative records, 43 of which met the inclusion criteria for this systematic review. Evidence emerged for institution demographics, institution type, institution climate, institution financial characteristics, and educational characteristics being related to various forms of victimization; institution setting (urban vs. rural) was not associated with victimization. Additionally, evidence was observed for institution location and size/density. Some factors, including institution type and campus demographics, operated differently for different forms of victimization. We highlight limitations of existing data, including variability in the measurement of victimization outcomes, lack of power to detect differences at the campus level, and challenges of creating a database on victimization that contains campus identifiers. We also reinforce calls for more intersectional research, both in terms of the types of victimization experienced by students as well as in the disproportionate impact victimization may have on students with marginalized identities.